F110. SYMPTOMATIC REMISSION WITH PALIPERIDONE PALMITATE 3-MONTHLY FORMULATION IN SCHIZOPHRENIA PATIENTS IN A CLINICAL PRACTICE SETTING. (9th April 2019) - Garcia-Portilla, M P; Llorca, P M; Maina, G; Bozikas, V P; Devrimci-Ozguven, H; Kim, S W; Bergmans, P; Usankova, I; Cherubin, P; Najarian, Dean; Pungor, K
Abstract: Background: Symptomatic remission (SR) is an important outcome for schizophrenia patients [1]. In pivotal trials, paliperidone 3-monthly formulation (PP3M) demonstrated favorable efficacy and tolerability in schizophrenia, including achievement of SR [2–4]. However, due to the selective nature of randomized clinical trials, populations studied may not be entirely representative of schizophrenia patients in real life. Methods: A prospective, single-arm, open-label, 52-week study (REMISSIO) was conducted in a naturalistic setting to assess the impact of conversion from paliperidone palmitate 1-month formulation (PP1M) to PP3M in patients with clinically stable schizophrenia. Patients aged 18–50 years with schizophrenia (DSM-5) were eligible to participate if they had been adequately treated with PP1M for ≥4 months (the last 2 doses of PP1M being the same) and had a baseline Positive and Negative Syndrome Scale (PANSS) total score <70. The initial dose of PP3M and subsequent dose changes (possible at clinicians' discretion) were made according to the product label [5]. The primary outcome was the number of patients who achieved SR (score ≤3 on PANSS items P1, P2, P3, N1, N4, N6, G5, and G9, maintained for ≥6 months) at the last observation carried forward (LOCF) endpoint [1]. Other outcomes included PANSS total and subscores, Clinical Global Impression of Change (CGI-C), and adverse events (AEs). The intent-to-treat (ITT) population comprised 305 patients from Europe, Middle East and Asia, who had received ≥1 dose of PP3M. Treatment response analyses were performed on the efficacy ITT population (n=303). Endpoint analysis using LOCF was performed, in addition to observed case analysis. Results: Patients had a mean (standard deviation; SD) age of 36.5 (8.0) years, 66% were male, and mean (SD) time since schizophrenia diagnosis was 9.2 (7.3) years. A total of 291 patients completed the 52-week study period. Mean (SD) first dose of PP3M was 363.6 (115.4) mg and mean (SD) mode dose during the study period was 362.2 (118.3) mg; all except 1 patient had the correct conversion from PP1M to PP3M. 4.9% and 3.6% of patients experienced PP3M dose decreases and increases, respectively. 58.0% of patients met the PANSS severity criterion at PP3M start, SR was achieved by 172 patients (56.8%) at LOCF endpoint, and Kaplan-Meier estimated median time to SR was 247 (95% confidence interval [CI], 189, 275) days. SR was achieved by 58.3% of patients on PP1M for >6 months vs. 50.9% of patients on PP1M for 4–6 months, and by 55.8% and 57.0% of patients switching from antipsychotic polytherapy or monotherapy, respectively. Mean PANSS total score for all patients improved from baseline (52.4 [SD 10.6]) to LOCF endpoint (–3.1 [95% CI, –4.1, –2.0]), and 67.8% of patients had achieved at least minimal improvement in their health status (according to CGI-C) at LOCF endpoint. A total of 29.4% of patients experienced ≥1 treatment-emergent AE considered related to study medication; 5.6% of patients reported bodyweight increase as an AE, and 4.6% of patients experienced possibly hyperprolactinemia-related AEs. Discussion: In conclusion, for the majority of schizophrenia patients, converting from PP1M in a naturalistic setting, PP3M achieved SR and maintained symptom stability. References: [1] Andreasen NC et al. 2005. Am J Psychiatry 162, 441–449. [2] Berwaerts J et al. 2015. JAMA Psychiatry 72, 830–839. [3] Savitz AJ et al. 2016. Int J Neuropsychopharmacol 19, 1–14. [4] Savitz AJ et al. 2017. Int Clin Psychopharmacol 32, 329–336. [5] TREVICTA prolonged release suspension for injection. Summary of Product Characteristics.